2019
DOI: 10.1155/2019/9687236
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Network Approach to Customer Requirements to Customized Product Model

Abstract: Customizing products based on customer needs is an irreversible trend, and many companies strive to provide customized products to customers in less time. Customer requirements are a key factor in the company's ability to provide customized products. In order to better meet customer needs, solve the problem of incomplete and inaccurate expression, and improve the correlation between customized product performance and customer demand, a customized product method based on Bayesian network is proposed. First, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Models that use BNs can make bidirectional inferences, capture the dependency between variables and manage uncertainties [38]. The BN´s theoretical basis is that if the probability of the initial node (variable) and the conditional probability among all nodes are determined, it is possible to quantify the distribution status of all nodes in the network [39]. A BN can be regarded as a compact representation of conjunction or joint probability distributions of a set of random variables (X1, X2, ..., Xn), as illustrated in Equation 1:…”
Section: The Proposed Approachmentioning
confidence: 99%
“…Models that use BNs can make bidirectional inferences, capture the dependency between variables and manage uncertainties [38]. The BN´s theoretical basis is that if the probability of the initial node (variable) and the conditional probability among all nodes are determined, it is possible to quantify the distribution status of all nodes in the network [39]. A BN can be regarded as a compact representation of conjunction or joint probability distributions of a set of random variables (X1, X2, ..., Xn), as illustrated in Equation 1:…”
Section: The Proposed Approachmentioning
confidence: 99%
“…In previous research [29], the DBC method has been used, which allows for customers to participate in the process of product design, resulting in modification and adjustment of the product to the customers' requirements. Therefore, in the context of processing and determination of products' quality level, the main methods used have been Kansei (KE) [24,[30][31][32], Quality Function Deployment (QFD) [33][34][35][36], Kano [16,34,37,38], and the Bayesian Network (Naive Bayesian Classifier) [39][40][41][42][43]. These methods were also integrated [31,32,34,38,44].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the above-mentioned Bayesian network (i.e., the so-called Naive Bayesian Classifier), is a probabilistic classifier based on independent, conditional assumptions. Examples in the literature, e.g., [39][40][41][42][43], apply the Bayesian network to adjust the level of product quality to meet customers' requirements. Forecasting or prediction of products' quality level has been analyzed in which authors applied a hidden Markov chain model [16,33,36].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, a growing number of emerging studies have addressed issues involved in offering a customized product [10][11][12]. Scholars have shown that offering a customizable product is an independent strategy in a monopoly market [13] and a competitive market, rather than in the context of vertical line extensions.…”
Section: Introductionmentioning
confidence: 99%
“…Equilibrium outcomes when the low-quality firm expands the product line. + (6τ − 9)μ 3 − 15τμ 2 − 8τ 2 μ)/(12…”
mentioning
confidence: 99%